Uji Efektifitas Antijamur Sediaan Nanogel Mengandung Zink Oxide Ekstrak Air Kulit Jengkol (Pithecellobium lobatum Benth) - monica valerie; Vera Estefania Kaban (LPPM Universitas Abdurrab, 2026)
Introduction: The skin of jengkol fruit contains metabolites such as saponins, tannins, flavonoids, and phenolic compounds that can inhibit microbial growth. Fungal infections caused by Candida albicans remain a health problem, necessitating the development of effective and safe antifungal preparations based on natural ingredients. Objective: This study aims to prove that nanogel preparations containing nanoparticles from water extracts of jengkol skin (Pithecellobium lobatum Benth.) have activity against Candida albicans fungi. Methods: The study was conducted experimentally using nanogels with concentrations of 2.5%, 5%, and 10%. Particle size was analyzed using a Particle Size Analyzer (PSA), while antifungal activity was tested using the well diffusion method on Potato Dextrose Agar (PDA) medium. Ketoconazole 2% was used as a positive control and the nanogel base as a negative control. The tests were conducted in triplicate. Results: The PSA test results showed that the nanogel particle size was in the nanometer scale, namely 38.86 nm; 38.80 nm; and 43.10 nm. The antifungal test results showed that the average inhibition zone diameter was 9.73 mm; 10.70 mm; and 11.76 mm, respectively, while the negative control did not show an inhibition zone. Statistical analysis showed significant differences between treatments (p<0.05). Conclusion: It can be concluded that the nanogel preparation has nanometer-sized particles and antifungal activity against Candida albicans